The sex-specific effects of RAGE signaling and type 2 diabetes on mouse cortical bone mechanics, structure, and material properties - Timothy Hung; Kaitlyn S. Broz; Remy E. Walk; Simon Y. Tang (Mechanobiology in Medicine)
Individuals with type 2 diabetes (T2D) are prone to fracture at numerous skeletal sites despite presenting with a higher bone mineral density (BMD). The accumulation of Advanced Glycation End-products (AGEs) in the bone tissues of patients with T2D could be contributing to this paradox of increased skeletal fragility with higher BMD. AGEs can also impair bone cell homeostasis via the receptor for AGEs (RAGE). To investigate the effects of diabetes, AGE accumulation, and RAGE signaling on mouse cortical bone, we utilized male and female leptin receptor-deficient (db/db) diabetic mice from three age groups ranging from 3 to 12 months of age, which were crossed with mice carrying constitutively active alleles for a RAGE nullifying point mutation (RAGE−/−). The morphological, mechanical and material outcomes of bone were measured using microCT, three-point bending, and AGE assays. We observed significant impairments dependent on age and sex to the bone matrix and whole-bone mechanical behavior due to diabetes, with some impairments alleviated by the deletion of RAGE. In older female diabetic mice, the removal of RAGE signaling prevented the deficits in bone mechanics, morphology, and tissue mineral density (TMD). Male diabetic mice without RAGE signaling exhibited improved material properties compared to wild type controls. The study demonstrated that bone impairments associated with T2D can be prevented with RAGE deletion, and T2D complications may be partially reversible with the therapeutic inhibition of RAGE signaling.